2008
DOI: 10.1073/pnas.0804506105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nonlinear electrostatics on transfer energies between liquid phases: Charge burial is far less expensive than Born model

Abstract: The widely used Born model describes the electrostatic response of continuous media using static dielectric constants. However, when applied to a liquid environment, a comparison of Born model predictions with experimental values (e.g., transfer free energies and pK a shifts) found that agreement is only achieved by using physically unrealistic dielectric constants for proteins, lipids, etc., and/or equally unrealistic atomic radii. This leads to questions concerning the physical origins for this failure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 31 publications
3
75
0
Order By: Relevance
“…Calculations based on MD simulations have also shown that the dielectric properties inside a protein can be comparable to the values of ε app listed in Table 1 (21-23). More recently, Freed and coworkers have pointed out that high apparent dielectric constants inside proteins can also result when dielectric saturation effects for the reference state (i.e., a model Glu in water) are ignored in the calculations (24). A rigorous computational study of the dielectric effects that determine the ionization properties of the internal Glu residues in SNase is underway in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Calculations based on MD simulations have also shown that the dielectric properties inside a protein can be comparable to the values of ε app listed in Table 1 (21-23). More recently, Freed and coworkers have pointed out that high apparent dielectric constants inside proteins can also result when dielectric saturation effects for the reference state (i.e., a model Glu in water) are ignored in the calculations (24). A rigorous computational study of the dielectric effects that determine the ionization properties of the internal Glu residues in SNase is underway in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…[17,34], our calculation shows that "ðrÞ has a sigmoidal shape as a function of the distance from the ion because of the dielectric saturation near the ion [35]. Because the primary contribution to the solvation energy arises from the local dielectric function near the ion, which is much reduced from the bulk value, the solvation energy is higher (less negative) than that predicted by the Born expression.…”
mentioning
confidence: 87%
“…The Born model has the virtue of being simple and intuitive in capturing the essential qualitative physics of solvation. However, quantitatively, the Born expression is known to be a poor description of the solvation of small ions [11], even in a one-component uniform liquid, because of the dielectric saturation (due to saturated dipole orientation) [15][16][17] near the ion. In a spatially inhomogeneous liquid or mixture, there is the additional effect of local density or composition response to the electric field of the ion.…”
mentioning
confidence: 99%
“…The linear-response treatment was motivated on the basis of continuum electrostatics, 11,12 and the role of the dielectric saturation was recently examined within the framework of continuum solvent model. 38,39 Our study employs an explicit-solvent model, and the effect of dielectric saturation is naturally incorporated if it exists. According to Fig.…”
mentioning
confidence: 99%